2021
DOI: 10.4103/1735-5362.323913
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Perilla frutescens seed oil rich in omega-3 fatty acid on dextran sodium sulfate-induced colitis in mice

Abstract: Background and purpose: Ulcerative colitis is a chronic inflammatory bowel disease that involves diffused inflammation of the large intestine. Omega-3 fatty acid (FA) has been known to regulate the inflammatory response associated with ulcerative colitis pathogenesis. Perilla frutescens is a valuable source of omega-3 FA and α-linolenic acid (ALA) contained in its seed oil. Therefore, the aim of this study was to evaluate the anti-inflammatory effect of Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Other types of unsaturated fatty acids found in P. frutescens seed oil were lauric acid, myristic acid, and arachidic acid. The amounts of these unsaturated fatty acids in P. frutescens seed oil were comparable with other reports [21,31,32]. M. oleifera oil contained several types of fatty acids, including cis-9-oleic acid (66.03 g/100 g), palmitic acid (7.91 g/100 g), and behenic acid (5.91 g/100 g).…”
Section: Plant Sterols Of P Frutescens M Oleifera and Mixed Seed Oilsupporting
confidence: 89%
“…Other types of unsaturated fatty acids found in P. frutescens seed oil were lauric acid, myristic acid, and arachidic acid. The amounts of these unsaturated fatty acids in P. frutescens seed oil were comparable with other reports [21,31,32]. M. oleifera oil contained several types of fatty acids, including cis-9-oleic acid (66.03 g/100 g), palmitic acid (7.91 g/100 g), and behenic acid (5.91 g/100 g).…”
Section: Plant Sterols Of P Frutescens M Oleifera and Mixed Seed Oilsupporting
confidence: 89%
“…Especially polyunsaturated fatty acids (PUFA) in which they occupied more than 50 % of total lipids found in perilla seed oil. The previous studied revealed that Thai perilla seed oil contains 61.51% of alpha linolenic acid (ALA), 16.55% of linoleic acid (LA)and 11.62 % of oleic acid (Kangwan et al, 2021). Similarly, in this study the ALA (53.18%) was report to be the most aboundunt fatty acids found in perilla seed oil, linoleic acid (22.17%), and oleic acid (14.90%).…”
Section: Discussionsupporting
confidence: 60%
“…For example, an increase in particular saturated fatty acids as a part of the so-called Western diet provokes IBD [ 333 ]. The data on polyunsaturated fatty acids-enriched diets, such as omega-3, in terms of gut health is contradictory, ranging from positive to negative effects [ 193 , 334 , 335 , 336 ]. Changes in the ratios of individual phospholipids were also found to accompany the ketogenic diet [ 337 ].…”
Section: Discussionmentioning
confidence: 99%